Learning to learn online - Page, Christina; Vincent, Adam; Alger, Marti; Kwantlen Polytechnic University. Learning Centre; Kwantlen Polytechnic University; BC Open Textbook Project; BCcampus (Kwantlen Polytechnic University, 2018)
"Learning to Learn Online helps you prepare for online learning success by introducing you to the online learning environment and your role as a learner within it. As you come to understand yourself as an self-directed learner, you will also be introduced to effective learning strategies: time management for online learners, information management, professional communication, and reading strategies. Welcome to your online learning journey!"--BC Campus website.
This bibliographic record is available under the Creative Commons CC0 "No Rights Reserved" license.
This work is licensed under the Creative Commons Attribution-NonCommercial-ShareAlike License.
Includes bibliographical references.
Description based on online resource; title from Website title page (viewed on February 26, 2019).
Keywords: Web-based instruction; Distance education; Internet in education; Electronic books